2003
DOI: 10.1308/003588403321661406
|View full text |Cite
|
Sign up to set email alerts
|

Reduced delays in A&E for elderly patients with hip fractures

Abstract: Published guidelines recommend early transfer of patients with hip fractures to hospital wards and avoidance of unnecessary delays in A&E. We describe a protocol whereby the liaison of an orthopaedic trauma co-ordinator with A&E reduced A&E-to-ward transfer times by 43%. Following introduction of the new protocol, 39% of hip fracture patients were in a ward bed within 3 h of admission to A&E compared to 4% previously. The new protocol also reduces administrative workload for the on-call orthopaedic SHOs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Techniques to expedite preoperative care can shorten operative delays, especially for those patients that have been medically cleared for surgery. For example, a recent systematic review as well as a prospective study of 116 patients found that dedicated trauma coordinators or hospitalists have been shown to be effective at fast-tracking patients with hip fractures to surgery by organizing operating room lists, perioperative care, securing hospital beds, and acting as a liaison with the radiology department and porting services 2965. A retrospective analysis of 139 patients found that a dedicated trauma operating room not only reduced the time to dynamic hip screw and closed femoral nailing procedures, but also allowed more of these surgeries to be performed during daytime hours, which may reduce postoperative complications 66…”
Section: Methods For Minimizing Surgical Delaymentioning
confidence: 99%
“…Techniques to expedite preoperative care can shorten operative delays, especially for those patients that have been medically cleared for surgery. For example, a recent systematic review as well as a prospective study of 116 patients found that dedicated trauma coordinators or hospitalists have been shown to be effective at fast-tracking patients with hip fractures to surgery by organizing operating room lists, perioperative care, securing hospital beds, and acting as a liaison with the radiology department and porting services 2965. A retrospective analysis of 139 patients found that a dedicated trauma operating room not only reduced the time to dynamic hip screw and closed femoral nailing procedures, but also allowed more of these surgeries to be performed during daytime hours, which may reduce postoperative complications 66…”
Section: Methods For Minimizing Surgical Delaymentioning
confidence: 99%
“…Studies have shown that treatment delays in the ED can be reduced with the use of ''fast-track'' programs. 16,17 However, to our knowledge, no one has performed a systematic analysis of the factors associated with wait times in the ED in the United States for patients with hip fracture. We performed a retrospective study evaluating patient, physician, and hospital factors that may affect time in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…A group of 50 patients with hip fractures admitted to a hospital via the ED in Manchester were studied prior to the introduction of a fast-track hip fracture protocol. The median ED-to-ward transfer time was reduced following its introduction by 43%, from 7 hours 4 minutes (range 2 hours 46 minutes to 11 hours 50 minutes) to 4 hours (range 1 hour 8 minutes to 11 hours 58 minutes, P < 0.0001) [70]. A major limitation of these studies of hip fracture-specific fast-track systems is that none studied their effect on waiting times for other patients in the ED.…”
Section: Question 4: In Hospital Eds Experiencing Overcrowding (Settimentioning
confidence: 97%